Inhibition Activity Alpha-Glucosidase Enzyme And Toxicity From Ethanol Extract Of Caulerpa Seaweed - Anisa Mulyani; Warsidah Warsidah; Mega Sari Juane Sofiana; Sukal Minsas; Riza Linda; Ikha Safitri (Barakuda'45, 2022)
Caulerpa is a green macroalgae found on Lemukutan Island, West Kalimantan. Caulerpa contains bioactive compounds that have potential to inhibit the alpha-glucosidase enzyme for people with diabetes mellitus. Inhibition of the alpha-glucosidase enzyme will have an impact on delaying glucose absorption. In addition, it is necessary to carry out a toxicity test to detect toxic effects and assess safety in the use of compounds. Therefore, the purpose of this study was to determine the inhibitory activity of the alpha-glucosidase enzyme and the toxicity of the ethanolic extract of Caulerpa seaweed in Lemukutan Island waters. Identification of secondary metabolites was determined from phytochemical tests. Inhibitory activity of the alpha-glucosidase enzyme determined by using enzymatic reactions, while the toxicity by method of BSLT. The showed that the percentage yield of Caulerpa ethanol extract was 3.66%. The content of bioactive compounds in the ethanolic extract of Caulerpa contains positive alkaloids, flavonoids, saponins, tannins, steroids, and phenolics. The inhibitory of the alpha-glucosidase enzyme had the highest percentage of inhibition with a concentration of 300 ppm indicating a percent inhibition of 16.85%. Toxicity obtained LC50 value of 598.19 ppm which is classified as low toxic.